Determinação de variação de volume na represa de Três Marias com o uso de radar altimétrico e imagens orbitais - Luiza Gontijo Alvares de Campos Abreu (2016)
Water sustains life on Earth and is fundamental to support the lifestyle of the world's population, being used for consumption, producing food, navegation and energy generation, mostly. Despite this importance, the water resources are used to their limits, with increasing populations and the need for even more water. Different satellite missions have instruments on board that measure the ocean level variations and now some of those instruments are being used in continental Waters with satisfactory results. Altimeters aboard the Envisat(RA-2) an SARAL(Altika) satellites are used to measure water level in inland water bodies. Studies about altimetry combined with the use of satellite imagery show the great potential of these techniques to estimate the quantities of water in rivers, lakes, wetlands and reservoirs and its variation in time in response to climate and environmental variables. The systematic and consistent monitoring of the water level variations in reservoirs is crucial for the development of policies and the application of actions related to the distribution and use of the stores water resource. This study presents a method to combine satellite altimetry and imagery from the Três Marias Hydroelectric Plant reservoir's lake to create a model in which the level or srface area can be estimated from one another, as well as the volume variations. In situ water level monitoring data from CEMIG were provided for the period from 2000 to 2015, the coeficients for the "level x area" and "level x volume" curves were used to validate the data generatedfrom remote sensing. For this time period were used 73 Landsat images from different dates to obtain the water surface area for the reservoir and 102 water level measurements from Envisat and Saral. The absolut difference mean between the area values from remote sensing and from the "level x area" from CEMIG is 9; 9 km2. The RMSE for the altimetry level measurements is 0; 7 m in relation to the in situ measurements from the station at the dam. The final model created with remote sensing data has an R2 = 0; 98 in relation to the in situ data fromCEMIG .